A estrutura do mercado de trabalho: análise dos municípios paranaenses - Carnevale, Rafaela Maria Graciano (2016)
The purpose of this research is to identify and analyze the variables that affect the level of employment and the labor market in the Parana municipalities. As methodology, it was used the panel data model and two indicators: i) the Location Quotient (LQ) which indicated that the branches of activities to show representative in the municipalities for the variables employment, wage and education; ii) Pearson Correlation Coefficient, which from the LQ calculation showed the correlation between the three variables. The results of the econometric model showed that the variable that most positively affects the level of employment in the State of Parana is the value added at basic prices of services, while other variables showed negative impact, such as: education, per capita GDP and population, which confirms in part the economic theory approached by research. The tertiary sector is the most employs, which pays the highest average wages and also the one with more education in the state in 2002, 2007 and 2012, and the primary sector is the one that presented fewer formal employees, lower average wage and lower education sector, however it has many specialized municipalities in generating employment and average wage. Finally, the correlation between the variables showed that most municipalities are located in the scale negative correlation between the variables, but this number has been decreasing, and in 2012 the correlation between wage and education has more municipalities with positive correlation. The correlation between employment and education is the one that has more municipalities with negative coefficient, that is, in these municipalities the sectors that employ most do not seek high education, at last, the correlation between average wage and average education shows that most municipal districts that pay higher wages are those that require more education.